Some introduction definition for optimization - Panuš, Jan (Univerzita Pardubice, 2004)
We can meet all the time with dilemmas of shortening of waiting time in different ways. What we mean is waiting time in automotive transportation. There are many theoretical pieces of knowledge for simplification of these dilemmas.We would like to introduce some basic optimization problems.
Keywords: Optimalizace; kombinatorická analýza; optimalizační modely; sítě